Gold nanostructured electrodes with enhanced plasmonic spectroscopy - Jiang, Yueyue (2013)
With the challenges of interfaced sciences and disciplines in materials sciences, chemistry, physics, and biology, as well as the demand in merging electronics and photonics at nanometer scale for miniaturized integrated circuits, an integration of functional complexities into the same platform emerges as the ultimate goal. This dissertation focuses on the development of novel and integrated nanostructured platforms for the combined development of multi-disciplinary sciences of plasmonics and electrochemistry. A tremendous synergy with this combination can be enhanced in producing a wealth of information by taking advantage of the unique and distinct electrical and optical properties of metals at nanoscale, and the strength of each technology. Single-nanoparticle electrodes, employing a combination of top-down and bottom-up approach, were firstly designed and fabricated with a facile and low-cost process. This particle electrode system could provide a diversity of plasmonic properties simply by varying the particle’s shapes and sizes. The surface-enhanced Raman spectroscopy (SERS) combined with electrochemistry has been used to develop an active plasmonic switch based on the ON/OFF resonance of the plasmonic response of the gold nanoparticles with the incident laser, via in situ electrochemical modulation. The plasmonic band of the single gold nanoparticle exhibited a giant shift when applying an external bias, as a result of the change of free electron density on the particle under alternate bias.